"Living together with dementia": Training programme for family caregivers – A study protocol. Issue 6 (November 2017) - Sousa, Lia; Sequeira, Carlos; Ferré‐Grau, Carme; Neves, Pedro; Lleixá‐Fortuño, Mar; Monteiro, Ana; Meireles, Joana; Pinto, Madalena; Gomes, Tiago
ABSTRACT : Highlights : The increased incidence of dementia places the family in the role of caregiver. It is important to create, to implement and to validate training programmes for family caregivers of people with dementia living at home. The programme "Living together with dementia" addressed in this protocol seeks to be a response to empower these caregivers. Introduction: : Due the increase incidence of Dementia, the creation, implementation and evaluation of the effectiveness of training programmes for family caregivers of people with dementia living at home should be a goal of health professionals. The aim of this paper is to describe the randomised control trial protocol that will assess the effectiveness of the training programme for family caregivers who care for people with dementia at home "Living together with Dementia". Methods: : Randomised control trial. Family caregivers of people with dementia in early and moderate stages will be recruited through a neurology appointment at the São João Hospital Centre, Porto‐Portugal. The inclusion criteria employed will be as follows: to be the main caregiver of the person with dementia; to be literate; the care target has dementia in early or moderate stage; the person with dementia does not suffer from any other severe mental pathology. Caregivers will be randomised and assigned to control and experimental groups. 3 assessment moments will take place: initial, after the intervention and a follow up of 3 to 6 months. The assessment instruments include a survey containing sociodemographic data, Caregiver Burden Scale, Caregiver Assessment Satisfaction Index and Caregiver Assessment Difficulties Index. The participants of the experimental group will be submitted to a 7‐week individual psychoeducational programme. The study was approved by the Health Ethics Committee of the São João Hospital Centre in September 2015. Discussion: : This programme might prove an asset to family caregivers of people with dementia living at home, since it pinpoints understanding and preparation of their role. It also facilitates the intervention of health professional, as it features as a guideline for their performance with this target population.